2004
DOI: 10.7326/0003-4819-140-1-200401060-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of Shared Decision Making, Informed Consent, and Simple Consent

Abstract: Enhancing patient choice is a central theme of medical ethics and law. Informed consent is the legal process used to promote patient autonomy; shared decision making is a widely promoted ethical approach. These processes may most usefully be seen as distinct in clinically and ethically important respects. The approach outlined in this article uses a model that arrays all medical decisions along 2 axes: risk and certainty. At the extremes of these continua, 4 decision types are produced, each of which constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
268
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(283 citation statements)
references
References 16 publications
7
268
0
8
Order By: Relevance
“…Some have taken the view that physicians should never make decisions for patients (McNutt, 2004). Others have suggested that patients should not be forced to make medical decisions if they prefer not to be involved (Whitney, McGuire, & McCullough, 2004). We support the view that patient-centered care should strive to respond to individual patient's needs and preferences when possible.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Some have taken the view that physicians should never make decisions for patients (McNutt, 2004). Others have suggested that patients should not be forced to make medical decisions if they prefer not to be involved (Whitney, McGuire, & McCullough, 2004). We support the view that patient-centered care should strive to respond to individual patient's needs and preferences when possible.…”
Section: Discussionsupporting
confidence: 72%
“…The main advantage of this item is that is refers to a situation where a true choice exists ("more than one method"), which is the situation generally touted as ideal for shared decision making (Whitney, McGuire, & McCullough, 2004). This item was also chosen because of its generality, i.e., preference for information not specific to laboratory tests, illness, side effects of medication, etc.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relational nature of this act places differing responsibilities on clinicians and patients to exchange information and to achieve a shared consciousness of uncertainty. This is a goal articulated in the ideal of shared decision making 52, 59 and in what Epstein has described as the achievement of “shared mind.” 60 …”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%
“…However, all medications also have the potential to cause harm (e.g., unpleasant side effects, allergic reactions) and most carry some risk of serious adverse effects. Principles of informed consent, informed and shared decision-making, and professional ethics all emphasize the importance of patients' understanding the potential harms and benefits of recommended therapies [2][3][4][5]. To help achieve this goal, many countries require that patients be given written medication information (WMI), usually in leaflet form, when they obtain a licensed medication [6][7][8].…”
Section: Introductionmentioning
confidence: 99%